Gestión de la comunicación y relaciones públicas - Arízaga Holguín, José Manuel (2019)
This research project arises from the need to assess the current context of behavior of the communication strategies promoted within the Cantonal Council for the Protection of Rights of the Pedro Carbo Canton of the province of Guayas and its effect on the inhabitants of the Sabanilla parish, with based on the premise that communication is an indispensable element for improving the scope of the objectives set by the entire organization that can be related to public objectives. This is possible thanks to a project with foundations of a descriptive and hermeneutic nature, which allows knowing the reality of the object of study and generating a diagnosis that allows its compatibility, deepening its relationships with the stakeholders involved…..